2019
DOI: 10.1101/656777
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

One-week exposure to South Indian Classical music clip having incremental variation in tempo and octave promotes better anxiety reduction among medical students – an EEG based study

Abstract: have non-trivial influence on the various neurological and psychological mechanisms underlying stress management. Considering the impact of this finding in selection of music clips for music therapy, further studies with larger sample size is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 77 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…Articles were also excluded if the use of music described was prospective rather than retrospective 38,39 ; if they described an opportunity for medical students to design and submit creative works without discussion of musical artworks created by medical students [40][41][42][43] ; or if the use of music was incidental in the service of another artform such as theatre, 44,45 video, [46][47][48] vodcast 49 or identity text. 50 Finally, articles were excluded if they described musical activities with a cohort of medical students not directly related to general medical education, for example, qualitative explorations of musical experiences in which medical students have been participants, 51 studies testing a hypothesis about the effects of music with a cohort of medical students under experimental conditions, [52][53][54][55][56][57][58][59][60][61][62] Research orientation, 64 methodology and limitations were identified through an appraisal of research quality using JBI Critical Appraisal checklists, [65][66][67][68] with each study rated independently by two authors and discussed until agreement was reached by the group.…”
Section: Methodsmentioning
confidence: 99%
“…Articles were also excluded if the use of music described was prospective rather than retrospective 38,39 ; if they described an opportunity for medical students to design and submit creative works without discussion of musical artworks created by medical students [40][41][42][43] ; or if the use of music was incidental in the service of another artform such as theatre, 44,45 video, [46][47][48] vodcast 49 or identity text. 50 Finally, articles were excluded if they described musical activities with a cohort of medical students not directly related to general medical education, for example, qualitative explorations of musical experiences in which medical students have been participants, 51 studies testing a hypothesis about the effects of music with a cohort of medical students under experimental conditions, [52][53][54][55][56][57][58][59][60][61][62] Research orientation, 64 methodology and limitations were identified through an appraisal of research quality using JBI Critical Appraisal checklists, [65][66][67][68] with each study rated independently by two authors and discussed until agreement was reached by the group.…”
Section: Methodsmentioning
confidence: 99%